A COMPARATIVE DISCUSSION AMONG THE GƏʿƏZ ACTS OF SAINT MARK THE EVANGELIST: THE SHORT RECENSION IN MULTIPLE-TEXT MANUSCRIPTS - Andualem Ermias Gebremariam (Әл-Фараби Атындағы Қазақ Ұлттық Университеті хабаршы шығыстану сериясы)
This article aims at comparing the Gəʿəz Acts of Saint Mark the Evangelist, one of the Four Evangelists and of the 70/72 Disciples of Jesus Christ. His Vita is regarded as it was originally composed in Greek and translated into Gəʿəz in the 4th century CE. The Gəʿəz texts, which all deals with the combat and martyrdom of the Saint, are preserved in distinct extant manuscripts with different recensions, in single and multiple-text manuscripts. The texts of the multiple-text manuscripts, in which this article is considered, are short and found in three discrete recensions. Based on the data collected from the aforementioned sources, comparison and analysis of the texts were carried out with a qualitative method. Eventually, based on the comparison of the three texts, it is indicated that each text could be transmitted through its own distinct line of recension, for each text contains discrete features in wordings, names and formulation of details. Keywords: Comparison, Gəʿəz Acts, Recension, Mark the Evangelist and Multiple-text Manuscript